Leto 1945 na Slovenskem v prizmi državljanskih vojn rimske pozne republike - Maver, Aleš (Studia Historica Slovenica, 2016)
Although many limitations must be observed, there are still some obvious structural similarities regarding the phenomenon of civil strife or rather civil war between the Rome of the 2nd and 1st centuries BC and Slovene lands in the 20th century. Destiny of the vanquished reached its the most characteristic form in the framework of the civil wars of the Roman Republic in the proscription lists. On the other hand, the victorious in such conflicts almost without exception tried to depict their successes as an important contribution to the spread of Roman influence. Octavian was the most successful in shaping of his own historical image, although already Sulla tried to influence it. Of course, in the Roman case there was neither a change of the ruling elite nor any major revolutionary upheaval.
Keywords: 1.-2.st.pr.n.št.; 1941-...; antika; državljanska vojna; Rim; Slovenija; vojna taktika